Hyperpolarization-activated cyclic nucleotide-gated gene signatures and poor clinical outcome of cancer patient / Phan Nhut Nam, Huynh Thanh Tung, Yen-Chang Lin - Phan, Nhut Nam
We investigated the mRNA expression of hyperpolarization-activated cyclic nucleotide-gated genes (HCN1-4) in multiple types and subtypes of cancers.